1989
DOI: 10.1128/aem.55.7.1787-1795.1989
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan Grazing and Bacterial Production in Stratified Lake Vechten Estimated with Fluorescently Labeled Bacteria and by Thymidine Incorporation

Abstract: In stratified Lake Vechten, The Netherlands, protozoan grazing was estimated on the basis of uptake of fluorescently labeled bacteria and compared with bacterial production estimated on the basis of thymidine incorporation. By using a grazer-free mixed bacterial population from the lake in continuous culture, an empirical relationship between cell production and thymidine incorporation was established. Thymidine incorporation into total cold-trichloroacetic-acid-insoluble macromolecules yielded a relatively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 34 publications
(56 reference statements)
6
30
0
Order By: Relevance
“…The literature data and the Upton Lake data are based on epilimnion communities only. Recent field studies in lakes also provide evidence for slow bacterial turnover times in the epilimnion, metalimnion, and hypolimnion (Sanders et al 1989;Bloem et al 1989). We conclude that community turnover times of planktonic bacteria in Upton Lake and in most systems are considerably > 1 d.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The literature data and the Upton Lake data are based on epilimnion communities only. Recent field studies in lakes also provide evidence for slow bacterial turnover times in the epilimnion, metalimnion, and hypolimnion (Sanders et al 1989;Bloem et al 1989). We conclude that community turnover times of planktonic bacteria in Upton Lake and in most systems are considerably > 1 d.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies have considered the relationship between bacterial growth and losses due to grazing and have inferred that growth and grazing are in close balance (McManus and Fuhrman 1988;Sanders et al 1989;Bloem et al 1989). On the other hand, Sherr et al (1989) made simultaneous measurements of growth and protozoan grazing and found that growth estimates consistently exceeded grazing estimates in a Georgia estuary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phagotrophic protists in the nannoplankton, flagellates, and 10 to 20 m ciliates are likely to have major roles as consumers of picoplanktonic primary production as well as of the secondary production of heterotrophic bacteria [37]. Phagotrophic protists are also responsible for much of the regenerative flux of nitrogen and phosphorus in the sea [38,39], and they can serve as a vital food resource for metazoans [40].…”
Section: Chlorpyrifosmentioning
confidence: 99%
“…For around two decades, the role of protozoa, in particular HNF, in controlling bacterial production in various types of aquatic systems has been demonstrated by different authors (Azam et al, 1983;Bloem et al, 1989;Servais et al, 2000). By efficiently feeding on bacteria, protozoa can channel up bacterial production to upper trophic levels, provided that metazooplankton actually prey upon them.…”
Section: Introductionmentioning
confidence: 99%